2016
DOI: 10.1016/j.matdes.2016.01.072
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and degradation mechanism in simulated body fluid of biomedical Mg–Zn–Ca alloy processed by high pressure torsion

Abstract: :In this paper, biomedical Mg-Zn-Ca alloy was processed by high pressure torsion (HPT) up to a maximum of 5 revolutions at room temperature and 7.5GPa. The microstructures of as-received material and HPT material were studied, as well as the corrosion properties and degradation mechanism of the alloy immersed in simulation body fluid (SBF). It revealed that the average grain size of as-received material was 11μm and most of the second phases distributed along the grain boundaries. The corrosion pits formed nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(24 citation statements)
references
References 40 publications
(40 reference statements)
0
22
0
1
Order By: Relevance
“…It should be noted that in this study a 0.1 M Cl -, with relatively high ohmic resistance, was used as the aggressive ion whereas earlier research involved more corrosive environments such as 0.62 M [Cl] -(3.5 wt% NaCl) which may persistently attack the surface and break down and change the chemistry corrosion product [9,10,13,43]. On the other hand, using passivating rather than corrosive solutions such as a simulated body fluid leads to an improvement in the protective oxide layer and corrosion behavior in each turn of the HPT process compared both to earlier turns and to the original extruded condition [22,23,82].…”
Section: Post-exposure Microstructural Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that in this study a 0.1 M Cl -, with relatively high ohmic resistance, was used as the aggressive ion whereas earlier research involved more corrosive environments such as 0.62 M [Cl] -(3.5 wt% NaCl) which may persistently attack the surface and break down and change the chemistry corrosion product [9,10,13,43]. On the other hand, using passivating rather than corrosive solutions such as a simulated body fluid leads to an improvement in the protective oxide layer and corrosion behavior in each turn of the HPT process compared both to earlier turns and to the original extruded condition [22,23,82].…”
Section: Post-exposure Microstructural Observationsmentioning
confidence: 99%
“…However, high-pressure torsion (HPT) is an SPD process that has an established capability in producing significant grain refinement in a range of Mg alloys and, more important, the processing can be effectively conducted at room temperature without the development of segmentation or cracking in the base metal [17,18]. Although the effect of various SPD processes on corrosion of magnesium was investigated thoroughly [5,6,8,12,[19][20][21], nevertheless little attention was devoted to the development of electrochemical behavior in the HPT-processed Mg alloys [9,10,[22][23][24] where reports have centered mainly on noting that more refined grains lead to a more homogenous corrosion. In practice, processing by HPT permits a study of corrosion behavior over a wide range of grain sizes and grain size distributions [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The grain size was reduced from 46 µm to 1-5 µm after the ECAP process and the alloy samples processed for 4 passes showed the lowest corrosion rates of approximately 6mm/year after 27 h of in vitro immersion and 1.1 mm/year after 60 days of in vivo implantation. Zhang et al [198] investigated the in vitro corrosion behavior of biomedical Mg-Zn-Ca alloy produced by high pressure torsion (HPT) up to 5 revolutions at room temperature and 7.5 GPa. It was observed that the HPT process caused grain refinement from 11 µm to 130-150 nm and a uniform distribution of the secondary phase.…”
Section: Mechanical Treatmentsmentioning
confidence: 99%
“…Many papers have reported the formation of ultrafine grained structures in pure magnesium [3][4][5][6] and AZ31 [7][8][9][10][11] , AZ61 12 , AZ80 13 , AZ91 [14][15][16] , ZK60 [17][18][19] , Mg-Zn-Y 20,21 , Mg-Gd-Y-Zr 22,23 , Mg-Zn-Ca [24][25][26][27] and Mg-Dy-Al-Zn-Zr 28 alloys. The processed alloys exhibit improved strength but also some papers report superplastic behaviour 16,19,22,29,30 , improved hydrogen storage properties 3,[31][32][33][34][35] and improved corrosion resistance 24,27,36 . Formation of ultrafine grained structures and improved strength are also observed in other metallic materials processed by HPT.…”
Section: Introductionmentioning
confidence: 99%